Keragaman Somaklonal pada Krisan (Dendranthema grandiflora Tzvelev) Secara In Vitro dengan Menggunakan Kolkisin - Nilahayati Nilahayati (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Variation of Somaclonal on Krisan (Dendranthema grandiflora Tzvelev) by In Vitro With Colkisin ApplicationABSTRACT. The purpose of this research induced somaclonal variation in four Chrysanthemum (Dendranthema grandiflora Tzvelev) cultivars by using colchisine through in vitro culture. The research design was factorial completely randomized design with ten replications. The first factor consisted of four Chrysanthemum cultivars namely Fiji White, Puma Putih, Fiji Dark and Stroika. The second factor comprised of six levels treatment of colchicine concentrations i.e. 0, 0.01, 0.025, 0.05, 0.075 and 0.1% w/v. The result showed that the growth of plantlet after treatment of colchicines much slower than control. The treatment of colchicines was reducing the shot initiation, plantlet high, number of leaves and nodes, number of roots and roots length but increased leaf chlorophyll content.